Síntese, caracterização e avaliação antimicrobiana de novos compostos amidoésteres e diésteres derivados da ftaloilglicina e da tetracloroftaloilglicina - Oliveira, Rafael Farias de (2021)
Infections caused by multidrug-resistant bacteria are very difficult to treat due to the action of antibiotics due to their ability to develop resistance. The development of new drugs and the rational use of antibiotics is of fundamental importance, being the main measures to prevent or decrease bacterial resistance. Among heterocyclic compounds, isoindoline-1,3-dione (phthalimide) represents an important building block for the planning and development of new varieties of drugs, knowing that compounds with this structural block have a great diversity of biological activities such as antibacterial, antifungal, analgesic, anti-inflammatory, antiviral, antitumor, analgesic, anticonvulsant, among others. In this work, we describe the synthesis, characterization of 27 unpublished heterocyclic compounds derived from phthaloylglycine and tetrachlorophthaloylglycine through SN2 reactions with N-Aryl-2-chloroacetamides and alkyl 2-chloroacetates. All new amidoester and diester compounds have been properly characterized by IR spectroscopic techniques, 1H and 13C RMN and crystallographic studies. The reactions showed yields varying from 77-95% for esters amides and 38-75% for diesters. In silico studies showed that all 27 compounds followed Lipinski's “rule of 5”, which indicates good oral bioavailability during drug administration, thus being a good candidate for a new drug. Structural data from crystallographic and theoretical studies of starch 47a were compared. The results of the antimicrobial tests showed that the diesters 48h and 48i showed antibacterial activity with CIM 3,072 μmol mL-1 and the diesters 48a-c, 48e, 48g and 48h-i showed antifungal activity with MIC ranging between 0,191-3,693 μmol mL-1. The 49a-i tetrachlorinated diesters showed antibacterial activity with MIC ranging between 0,560-2,386 μmol mL-1 and antifungal activity with MIC ranging between 0,144-0,280 μmol mL-1. Compounds 47a-i did not show antimicrobial activity for the strains tested.